Body composition analysis in adults with osciable blood pressure - Slusar Adriana; Vizitiu Lakhdari Elena (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement)
Previous studies have suggested that physical activity in water can favorably influence body composition and blood pressure, having beneficial effects on cardiovascular health and reducing the risk of developing hypertension. Body composition and blood pressure are essential factors in assessing general health, having a significant impact on the risks of developing cardiovascular diseases. Hypothesis of the work: It is assumed that by practicing hydrokinetotherapy, the body composition of adults with oscillating blood pressure can be improved, and blood pressure oscillations can be reduced, thus contributing to improving general health. The purpose of this work is to analyze the impact of hydrokinetotherapy on body composition and blood pressure variability in adults, with the objective of highlighting the potential of this form of therapy in optimizing cardiovascular health and in effectively managing blood pressure fluctuations. Objectives of the work: Assessment of body composition before and after a hydrokinetotherapy program; Monitoring blood pressure during the program to observe changes in its oscillations. Determining the relationship between hydrokinetotherapy practice, body composition, and blood pressure stability. Further research is needed to validate the effectiveness of this hydrokinetotherapy program in different population groups and to investigate the mechanisms by which it affects physiological parameters.